(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Targeted this study underlined the importance of the adoption of international accounting standards and their impact on the process of tax for settlements to achieve taxation justice the application on a sample of foreign banks investing in the local environment in order to achieve many of the objectives: • Definition of the concept of justice for settlements taxation. • To identify the impact of adopting international accounting standards in achieving the justice for settlements taxation. • To determine the impact of the adoption of international accounting standards in attracting foreign investment. They are summed up the problem of the study in the light of the nature of the problem and questions associated with not to adopt the tax authority in Iraq to the financial lists the foreign companies working in the country and the stomach in accordance with international accounting standards for the purposes of tax for settlements which leads to achieving equitable tax for settlements as well as the promotion of tax evasion. To achieve the objective of the study and testing of the premise was the selection of one of the foreign banks investing in the local environment to know the impact of international accounting standards in the process for settlements taxation and achieve justice for settlements taxation and the results that the presence of a positive impact for the use of international accounting standards for foreign companies investing in the local environment.